Immunization with a Synthetic Human MUC1 Glycopeptide Vaccine against Tumor‐Associated MUC1 Breaks Tolerance in Human MUC1 Transgenic Mice. (7th August 2017) - Stergiou, Natascha; Glaffig, Markus; Jonuleit, Helmut; Schmitt, Edgar; Kunz, Horst
Abstract: Breaking tolerance is crucial for effective tumor immunotherapy. We showed that vaccines containing tumor‐associated human MUC1 glycopeptides induce strong humoral antitumor responses in mice. The question remained whether such vaccines work in humans, in systems where huMUC1 is a self‐antigen. To clarify the question, mice transgenic in expressing huMUC1, mimicking the self‐tolerant environment, and wild‐type mice were vaccinated with a synthetic vaccine. This vaccine comprised STn and Tn antigens bound to a MUC1 tandem repeat peptide coupled to tetanus toxoid. The vaccine induced strong immune responses in wild‐type and huMUC1‐transgenic mice without auto‐aggressive side effects. All antisera exhibited almost equivalent binding to human breast tumor cells. Similar increases of activated B‐, CD4 + T‐, and dendritic cells was found in the lymph nodes. The results demonstrate that tumor‐associated huMUC1 glycopeptides coupled to tetanus toxoid are promising antitumor vaccines. Abstract : Booster shot for cancer immunotherapy : A synthetic human tumor‐associated MUC1 glycopeptide vaccine that contains tetanus toxoid as a carrier protein is able to induce a strong humoral immune response within human MUC1 transgenic mice. These results suggest that the induction of a selective immune response to an altered cancer‐related glycopeptide antigen is possible without autoimmune side effects against the self‐antigen.